Layanan Konseling Individual dengan Teknik Self-Talk dalam Menumbuhkan Resiliensi Remaja - Padila Rizki Amelia; Kusnadi; Bela Janare Putra (ScidacPlus, 2024)
This study is entitled Implementation of Individual Counseling Services with Self-talk techniques in fostering adolescent resilience (Case study on client L at the Pelangi Palembang Orphanage), where this study aims to determine the implementation of individual counseling services using self-talk techniques in fostering adolescent resilience living in the Orphanage. This research method uses qualitative descriptive with a case study approach. Data collection techniques used include observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusions. The results obtained from the research conducted are that client L has had significant changes because client L already has resilience in himself after following the counseling that has been given, client L has begun to be able to identify his negative thoughts and has begun to be able to evaluate or change his negative thoughts into positive thoughts by using self-talk techniques.